Land Seismic Repeatability Prediction from Near Surface Investigation - Al-Jabri, Yousuf; Urosevic, Milovan (SEG, 2010)
High seismic repeatability is critical to the monitoring program of the Naylor Field because of the small time-lapse effect related to CO2 injection into a depleted gas reservoir (Naylor). To understand the effect of changing ground conditions on repeatability, we conducted so-called “micro-array” investigation of the near-surface layers at this site. A feature of the injection test site area is the near-surface karst topography. In such geological terrain, a change in water table level can influence the seismic response and cause changes in the seismic wave scattering pattern. Hence the aim of micro-array measurements was to determine the properties of the near surface layers during the wet and dry seasons. This could help us understand and ultimately predict the seismic response and hence survey repeatability at a given site.Measurements of seismic response due to near surface property changes (seasonal) could help optimise the design of time lapse surveys which ultimately yields improved survey differencing. Measured elastic properties of the near surface are used to produce seismic response and predict repeatability as a function of the variable soil conditions. Comparison of numerical and field data is finally used to verify the validity of this approach. In this study we investigated the variation of elastic properties of both top soil and the deeper rugose clay-limestone interface as a function of water depth level. Such tests in fact simulate the measurements conducted in dry and wet seasons and help evaluate the effect of these seasonal variations on the seismic signature, which is then analysed in terms of non-repeatability. In this study, we use both micro-borehole (micro VSP) and micro-refraction arrays to analyse directional properties of the near-surface. Finally, numerical tests were performed with calibrated soil parameters.